PRDX5 and PRDX6 translocation and oligomerization in bull sperm: a response to cryopreservation-induced oxidative stress - Mostek-Majewska Agnieszka; Bossowska-Nowicka Magdalena; Słowińska Mariola; Ciereszko Andrzej (Cell Communication and Signaling)
Abstract Cryopreservation of bull sperm, crucial for breeding and assisted reproduction, often reduces sperm quality due to oxidative stress. This study examines how oxidative stress during cryopreservation affects peroxiredoxin 5 (PRDX5) and peroxiredoxin 6 (PRDX6) proteins, leading to their translocation and oligomerization in bull sperm. Increased reactive oxygen species (ROS) and nitric oxide (NO) levels were linked to reduced mitochondrial potential, higher DNA fragmentation, and increased membrane fluidity, prompting PRDX5 to move intracellularly and PRDX6 to the cell membrane. Under cryopreservation, these proteins formed high molecular weight oligomers, that may shift from peroxidase to chaperone roles. Their interaction with Toll-like receptor 4 (TLR4) may be key to their intracellular transport. On the other hand, the presence of PRDX5 and PRDX6 in exosomal vesicles suggested a potential mechanism for their transport into sperm cells. Using Imaging Flow Cytometry and various PAGE techniques, the study detected PRDX5 and PRDX6 in different sperm locations and analyzed their oligomer formation. These findings highlight the adaptive roles of PRDX5 and PRDX6 in protecting sperm cells, offering insights that could improve cryopreservation protocols in animal breeding and human reproductive medicine, and advance our understanding of the oxidative stress response in sperm cells.